RECOGNITION FOR THE AUTISTIC IN KARAN JOHAR'S MY NAME IS KHAN (2010): A SOCIOLOGICAL APPROACH - PURWANINGSIH , YUSUF (2011)
This study investigates the recognition for the autistic that is reflected in My Name is Khan viewed from sociological approach. The aims of this study are to analyze the structural elements of the movie and to analyze the movie based on sociological perspective. This study belongs to qualitative study. In this method, the writer uses two types of d ata source, namely primary and secondary data source. The primary data source and the object of the study is the movie itself, meanwhile the secondary one is any literature related to this study for example reading some other resources related to the movie. The writer collects the data from both primary and secondary data source in sort of document as evidence. The technique of analyzing data is descriptive. Having analyzed this movie, the writer dr aws some conclusions as follows. First, based on the structural analysis, My Name is Khan suggests that an autist person is same as others. Second, based on the sociological analysis, Karan Johar’s My Name is Khan movie describes a close relationship to social condition between Indian and America.